Nonlinear dynamics of a rack-pinion-rack device powered by the Casimir force. - Miri, M; Nekouie, V; Golestanian, R (2010)
Using the lateral Casimir force-a manifestation of the quantum fluctuations of the electromagnetic field between objects with corrugated surfaces-as the main force transduction mechanism, a nanomechanical device with rich dynamical behaviors is proposed. The device is made of two parallel racks that are moving in the same direction and a pinion in the middle that couples with both racks via the noncontact lateral Casimir force. The built-in frustration in the device causes it to be very sensitive and react dramatically to minute changes in the geometrical parameters and initial conditions of the system. The noncontact nature of the proposed device could help with the ubiquitous wear problem in nanoscale mechanical systems.